Endoscopic Findings in patients with iron deficiency anemia over 60 years of age - اسماعيل حماد,; فراس حسين ,; غسان منصور, (Latakia University Journal -Medical Sciences Series, 2023)
Background: The aim of this study is to analysis of endoscopic findings in elderly patients with iron deficiency anemia. Materials and Methods: An analytic descriptive study was conducted in elderly patients with a diagnosis of iron deficiency anemia, in Tishreen University Hospital between 2021 and 2022. Results: A total of 96 patients, 59 males (61.5%) and 37 females (38.5%) were included in the study, with an average age of 73.4 ± 7.7 years. The findings of upper gastrointestinal endoscopy were: Duodenal Ulcer(26%),Gastropathy(24%),Gastric Ulcerations(17.7%), Gastric Ulcer(12.5%). The findings of lower gastrointestinal endoscopy were:Right Colon Cancer(24%),Ulcerated Polyps(22.9%),Left Colon Cancer(17.7%),Angiodysplasia(14.6%). A significant statistical relationship was established between Gastric Cancer and the very advanced age group(older than 80 years), and between Colon Cancer and the male gender in the studied age group.